FOUR NEW SPECIES OF ARENGA (PALMAE) FROM INDONESIA - Mogea, Johanis Palar (REINWARDTIA, 2004)
Â MOGEA, JOHANIS P. 2004. Four new species of Arenga (Palmae) from Indonesia. Reinwardtia 12 (2): 181 â 189. -- Arenga distincta from Borneo and A. longipes, A. plicata, and A. talamauensis from Sumatra are described and illustrated for the first time. The descriptions are followed by information regarding the habitat and geographical distribution, and notes on morphological similarities with other, presumably related species.Leaves of A. longipes and A.talamauensis are paripinnate while the other two species are imparipinnate.